Comparing the effect of aromatase inhibitor (letrozole) + cabergoline (Dostinex) and letrozole alone on uterine myoma regression, a randomized clinical trial. (March 2017) - Sayyah-Melli, M.; Mobasseri, M.; Gharabaghi, P.M.; Ouladsahebmadarek, E.; Rahmani, V.
Abstract: Objective: To evaluate the effect of letrozole in combination with cabergoline and letrozole alone on regression of symptomatic uterine myomas in women of reproductive age. Design: Randomized controlled clinical trial. Setting: University hospital. Patients: Ninety-one women of reproductive age were enrolled in the study and 88 women were eligible. Eight participants were excluded from the study. Interventions: Eighty women of reproductive age with symptomatic myomas >4 cm were evaluated in two groups. Participants in Group 1 received 2.5 mg letrozole once daily and cabergoline 0.5 mg/week from the first day of the menstrual cycle for 12 weeks, and participants in Group 2 received letrozole alone. Main outcome measures: Changes in uterine size and volume; myoma size, volume and number; and side effects of treatment. Results: Overall, 76 patients completed the study. Compared with baseline values, mean uterine volume was reduced significantly in both groups (p = 0.01), and there was no significant difference between groups (p = 0.99). The mean number of dominant myomas was reduced significantly in both groups (p = 0.03), with no significant difference between groups (p = 0.6). The mean volume of myomas was reduced significantly in both groups (p = 0.01), with no significant difference between groups (p = 0.45). Although a significant decrease in number and volume of myomas was documented in each group (p < 0.05), the intergroup analyses did not reveal significant differences between the two groups in terms of the change in number (p = 0.28) and volume (p = 0.96) of myomas. Headache was significantly more common in the letrozole + cabergoline group (nine vs two cases, p = 0.02), but the two groups were comparable for the remaining minor side effects. Conclusion: This study showed that 12 weeks of treatment with letrozole with and without cabergoline improved the size and volume of the uterus and myomas, led to symptom improvement, and could be used for short-term treatment prior to surgery or fertility programmes. Condensation: Condensation letrozole in combination with cabergoline in the management of uterine fibroids.